The In Vitro Digestibility of Complete Silage From Sorghum bicolor (L.) Moench Ingredient using Different Additives - Oktovianus Rafael Nahak; Paulus Klau Tahuk; Gerson Frans Bira; Yohanes Baptista Ambone (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
This study aimed to determine the in vitro nutrient digestibility of complete silage from Sorghum bicolor (L.) Moench using different additives. The method used was a completely randomized design containing 4 treatments and 4 replications, namely, R1: Sorghum bicolor (L.) Moench + L. leucocephala (without additives/control), R2: Sorghum bicolor (L.) Moench + L. leucocephala + 20% rice bran + 10% rock sugar, R3: Sorghum bicolor (L.) Moench + L. leucocephala + 20% corn meal + 10% rock sugar, R4: Sorghum bicolor (L.) Moench + L. leucocephala + 20% pollard + 10% rock sugar. The additive material percentage was calculated based on the chopped weight of Sorghum bicolor (L.) Moench and L. leucocephala. The data obtained were assessed by the analysis of variance, and then continuously analyzed by the Duncan's multiple range test. The Sorghum bicolor (L.) Moench plants were harvested on 70 days after planting and withered for 3 hours to reduce the moisture content, and then chopped at 3 cm size. The chopped results were mixed with the additive materials based on the treatments and their percentages applied, and then moved to the plastic container (silo), the mixture that was moved into the silo was suppressed to make the chopped layer solid (anaerobic principal). Ensilage process was stood for 21 days. The complete silage was removed, and its in vitro nutrient digestibility was analyzed. The results showed that the use of additives could improve the dry matter, organic matter, N-NH3, and VFA digestibility of complete silage from Sorghum bicolor (L.) Moench. It can be concluded that the additive supplementation of 20% pollard and 10% rock sugar can improve the dry matter, organic matter, N-NH3, and VFA digestibility of complete silage from Sorghum bicolor (L.) Moench.